The official history of criminal justice in England and Wales - Newburn, Tim, author. Link
1 online resource.
Keywords: "This is the fifth and final volume in the Official History of Criminal Justice in England and Wales. This volume covers the uneven and often irresolute evolution of policing from the late 1940s to the end of the 1990s, concentrating on the impact of a succession of scandals on the reputation and regulation of the police; and the fluctuating relations between central government, local authorities and police forces in shaping the control of police funding, policy and organisation, particularly in response to a growth in the scale and intensity of social protest, and, above all, on the shifting sands of the policing of public order illustrated in the prolonged miners' strike and urban unrest of the 1980s. It is a complement to earlier volumes in the series that focused on the liberalisation of the laws on capital punishment, abortion and homosexual relations between adult men in the 1960s; the founding of the Crown Court in 1971 and the Crown Prosecution Service in 1985; transformations in penal policy, and the politics of law and order. It will be of much interest to students of British political history, criminology and sociology"--